Preparation, characterization, and performance of 4A zeolite based on opal waste rock for removal of ammonium ion - Zongshan Wu; Jingjing Xie; Haibo Liu; Tianhu Chen; Peng Cheng; Can Wang; Dianchao Kong (Adsorption Science & Technology)
In this study, 4A zeolite was prepared from opal waste rock by hydrothermal method and applied in ammonium ion adsorption. To optimize synthesis conditions, the effect of crystallization time (1–8 h), crystallization temperature (65–115°C), Na 2 O/SiO 2 (0.6–2.0), H 2 O/Na 2 O (20–70), and SiO 2 /Al 2 O 3 (1.0–3.5) was investigated. X-ray diffraction, scanning electron microscope imaging, cation exchange capacity, static water adsorption, Fourier transform infrared spectroscopy, and N 2 adsorption–desorption isotherm were used for assessing properties of 4A zeolite. Adsorption experiments were performed by 1.0 g l −1 4A zeolite with NH 4 + solution (5–300 mg l −1 ) for 4 h at room temperature. The experiment results revealed with a crystallization time of 3 h, a crystallization temperature of 85°C, Na 2 O/SiO 2 =1.0, H 2 O/Na 2 O = 40, and SiO 2 /Al 2 O 3 =2.0, the 4A zeolite synthesized had excellent performance with cation exchange capacity of 2.93 mmol (g dry zeolite) −1 and static water adsorption of 22.3%. The adsorption process was described by Freundlich model (R 2 >0.99) and the maximum adsorption capacity could reach to 53.11 mg g −1 . The experimental results provided a novel approach for the utilization of opal waste rock, which is produced during the mining of opal-rich palygorskite, and for the synthesis of 4A zeolite and the removal of ammonium ion.